Medial meniscus extrusion is a determinant factor for the gait speed among MRI-detected structural alterations of knee osteoarthritis. Issue 3 (September 2021) - Arita, Hitoshi; Kaneko, Haruka; Ishibashi, Masayoshi; Sadatsuki, Ryo; Liu, Lizu; Hada, Shinnosuke; Kinoshita, Mayuko; Aoki, Takako; Negishi, Yoshifumi; Momoeda, Masahiro; Adili, Arepati; Kubota, Mitsuaki; et al.
Abstract: Objective: Knee osteoarthritis (OA) is one of the most common causes for reduction in gait speed. Research into the mechanism of underlying knee OA pain and other symptoms such as the reduction in the gait speed is essential to development of disease-modifying treatments for knee OA. We examined the magnetic resonance imaging (MRI)-detected structural alterations in knee joints those were associated with gait speed in knee OA patients. Design: In this cross-sectional study, structural alterations in knee joints of 74 knee OA patients (51 females; mean 72.2 years old) were evaluated by MRI, and subjects' gait speed was measured. Results: The mean self-selected gait speed of the subjects was 0.73 ​± ​0.21 ​m/s. A simple linear regression analysis revealed that MME was only correlated with the gait speed of the subjects with knee OA, while cartilage lesion, bone marrow lesion, subchondral bone cyst, subchondral cyst, osteophytes and meniscal pathology were not. A multiple regression analysis revealed that only MME was associated with gait speed (R 2  ​= ​0.484, p ​< ​0.001). The area under the receiver operating characteristic curve for determining <0.8 ​m/s of gait speed as evaluated by MME were 0.72 (95% confidence interval: 0.60–0.84). The relative risks at a cut-off <0.8 ​m/s for gait speed as evaluated by MME at 6.2 ​mm were 2.19 (1.28–3.46, p ​= ​0.01). Conclusions: MME was associated with and the determinant for gait speed among MRI-detected structural alterations in patients with knee OA, suggesting the importance for elucidating the etiology of MME for developing a disease-modifying treatment for knee OA.